EFFECT OF AUDIO-VISUAL HEALTH EDUCATION ON PSYCHOLOGICAL DISTRESS OF PERIOPERATIVE PATIENTS: A SYSTEMATIC REVIEW - Setiawan, Arif; Sriyono; Maryanti, Herdina (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Audiovisual health education for postoperative patients is a strategy used by health care providers to reduce psychological distress in postoperative patients. Health education improves the patient's adaptation to the anxiety associated with a surgical project. Methods: This study was a systematic review study of 4 databases, namely Web of Science, PubMed, EBSCO Host, and Scopus, with keywords “Audio-Visual